Reconstruction of the retroactive principle in the Indonesian criminal Law code based on the value of religious wisdom - Sri Endah Wahyuningsih; Muchamad Iksan (UNISSULA, 2017)
Indonesian Criminal Code that comes from Dutch heritage has to be reconstructed, because it is not in accordance with the state of Indonesia which is now already independent. One of the important principles in the Criminal Code that needs to be reconstructed is the retroactive principle contained in Article 1 paragraph (2) of the Criminal Code. The law can be retroactive as long as it benefits the defendant, not until the convicted person. The purpose of this research is to evaluate retroactive principle in Criminal Code seen from perspective value of religious wisdom, and ideal reconstruction of retroactive principle in next Criminal Code in accordance with perspective value of religious wisdom. Approach method in this research was done with normative juridical, the data used were secondary data by doing the extracting data bibliography, and data analysis were done by using qualitative descriptive method. Based on the values of religious wisdom, especially from the perspective of Islamic law in the case of any change of laws and regulations, in principle, non-retroactive principle (non-retroactive) is applied, but in certain cases the principle can be disregarded in accordance with the principles of